Ninth International Workshop on Principles of Software Evolution: In Conjunction With the 6th ESEC/FSE Joint Meeting 2007
DOI: 10.1145/1294948.1294968
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the "staged model for software evolution" to free/libre/open source software

Abstract: Research into traditional software evolution has been tackled from two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…This may be viewed as a refinement of the Rajlich and Bennett model, where developments done in one branch are propagated to another branch that is developed in parallel. Capiluppi et al have observed that in open-source projects a legacy system may be picked up and revived by a new set of developers, thus returning it to the evolution phase [9].…”
Section: Lifecycle Models For Long-lived Software Projectsmentioning
confidence: 99%
“…This may be viewed as a refinement of the Rajlich and Bennett model, where developments done in one branch are propagated to another branch that is developed in parallel. Capiluppi et al have observed that in open-source projects a legacy system may be picked up and revived by a new set of developers, thus returning it to the evolution phase [9].…”
Section: Lifecycle Models For Long-lived Software Projectsmentioning
confidence: 99%
“…Instead of using the model that was built mainly by observing traditional software development, Capiluppi et al [43] revised the staged model for its applicability to OSS evolution.…”
Section: -Exogenous Factorsmentioning
confidence: 99%
“…One could inadvertently misclassify dormant projects as "inactive"; projects could be renamed in the meantime, or even just moved to dedicated repositories. 3 The information on such inferred inactivity has relevant external effects: from an end-user's point of view, organizations and private users would not want to invest money or time to deploy or evaluate inactive projects, or those with few or no contributors to perform future maintenance. From a developers' point of view, the original authors should take the responsibility to inform others that they are no longer interested (or able) to support or enhance their project.…”
Section: Introductionmentioning
confidence: 99%
“…This would introduce one of the most powerful mechanisms in OSS development, namely the possibility for another developer to take over the project from one or more previous developers who lost interest in it [15,3]. Thus, we identified two key motivations for accurately labelling inactive or abandoned projects:…”
Section: Introductionmentioning
confidence: 99%